Knowledge, perceived risk and barriers to testicular self-examination among male university students in Uganda - Kanaabi Muliira, Joshua; Bbosa Nalwanga, Priscilla; Suubi Muliira, Rhoda; Nankinga, Ziada (Journal of Men's Health, 2012)
Testicular cancer (TC) is the most common malignancy among men aged 15–35 years and although Africa has one of the lowest prevalence rates, TC is often diagnosed late. The aim of this study was to describe TC knowledge, perceived risk and barriers to testicular self-examination (TSE) among young males in Uganda. Method: Self-administered questionnaires and a systematic random sampling technique were used to collect data from 323 male students in a Ugandan University. Results: The participants were mostly in the 18–22 years age range (59%) (mean age = 22 2.5 years). The majority of participants (87%) did not know what age group was most at risk for TC, when to perform TSE (71%) or whether testicular lumps are a sign of TC (77%). Participants mostly perceived their risk for TC as being either low (32%) or moderate (58%). The mean perceived risk for TC was 1.8 0.61 and few participants (14%) were performing TSE regularly. Most participants (80%) reported a lack of skill for performing TSE as well as perceiving TSE as embarrassing (87%) and time consuming (79%). Selfreported practice of TSE was found to be associated with different aspects of TC knowledge (P = 0.01). Conclusion: Young male Ugandans have little knowledge about TC and perceive their risk for this disease to be low. Findings show that having good knowledge about TC is associated with performing TSE. Implications for practice are that health care providers should scale-up health education about TC to empower young males with the knowledge and skills required for cancer preventive practices and behaviors. 2011 WPMH GmbH. Published by Elsevier Ireland Ltd.
Keywords: Young males; Testicular cancer; Knowledge; Risk; Cancer prevention